2006
DOI: 10.1007/s11547-006-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Doppler ed angio-RM nella valutazione della stenosi carotidea

Abstract: These data suggest that endarterectomy on the basis of Doppler US and CE-MRA can be considered appropriate. CEMRA was the best noninvasive imaging modality to detect plaque ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
(88 reference statements)
0
8
0
Order By: Relevance
“…Sensitivity and specificity were also better with contrast-enhanced MRA using Gd-DOTA than TOF-MRA when evaluated at the segment level, and the technical failure rate for contrast-enhanced MRA using Gd-DOTA was substantially (and statistically significantly, p<0.0001) lower than for TOF-MRA. A number of published clinical studies have shown that MRA is as accurate as conventional (x-ray) intra-arterial digital subtraction angiography in clinical situations such as lower-extremity atherosclerotic occlusive disease or carotid artery stenosis [12][13][14]. In these and other studies, MRA has demonstrated similar sensitivity and specificity to conventional x-ray angiography, with a predicted lower cost and lower risk due to the absence of injected iodinated contrast and vessel catheterization (i.e., lower invasiveness) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity and specificity were also better with contrast-enhanced MRA using Gd-DOTA than TOF-MRA when evaluated at the segment level, and the technical failure rate for contrast-enhanced MRA using Gd-DOTA was substantially (and statistically significantly, p<0.0001) lower than for TOF-MRA. A number of published clinical studies have shown that MRA is as accurate as conventional (x-ray) intra-arterial digital subtraction angiography in clinical situations such as lower-extremity atherosclerotic occlusive disease or carotid artery stenosis [12][13][14]. In these and other studies, MRA has demonstrated similar sensitivity and specificity to conventional x-ray angiography, with a predicted lower cost and lower risk due to the absence of injected iodinated contrast and vessel catheterization (i.e., lower invasiveness) [15].…”
Section: Discussionmentioning
confidence: 99%
“…A Class III study by D'Onofrio et al 61 prospectively evaluated 32 patients who either had carotid Doppler ultrasonography (DUS) or contrast-enhanced MRA and compared it to either digital subtraction angiography (DSA) or endarterectomy. Both had strong correlation in identifying stenosis, with both identifying 100% of surgical stenosis (defined as carotid stenosis of 60% to 99%).…”
Section: In Adult Patients Withmentioning
confidence: 99%
“…With the development of noninvasive magnetic resonance techniques and imaging technology, the diagnostic values of magnetic resonance angiography (MRA) and Doppler ultrasound (DUS) in CS are a current focus of research. In the diagnosis of CS, the results of these noninvasive examination methods are consistent with those of DSA; therefore, MRA and DUS, as noninvasive screening methods, may be suitable replacements for DSA (9)(10)(11)(12) DUS (CDUS) in detecting the extent of CS remain to be determined by large scale studies.…”
Section: Introductionmentioning
confidence: 82%